Rat hypocretin/orexin neurons are maintained in a depolarized state by TRPC channels. - Vesna Cvetkovic-Lopes (PLoS ONE, 2010)
In a previous study we proposed that the depolarized state of the wake-promoting hypocretin/orexin (hcrt/orx) neurons was independent of synaptic inputs as it persisted in tetrodotoxin and low calcium/high magnesium solutions. Here we show first that these cells are hyperpolarized when external sodium is lowered, suggesting that non-selective cation channels (NSCCs) could be involved. As canonical transient receptor channels (TRPCs) are known to form NSCCs, we looked for TRPCs subunits using single-cell RT-PCR and found that TRPC6 mRNA was detectable in a small minority, TRPC1, TRPC3 and TRPC7 in a majority and TRPC4 and 5 in the vast majority (∼90%) of hcrt/orx neurons. Using intracellular applications of TRPC antibodies against subunits known to form NSCCs, we then found that only TRPC5 antibodies elicited an outward current, together with hyperpolarization and inhibition of the cells. These effects were blocked by co-application of a TRPC5 antigen peptide. Voltage-clamp ramps in the presence or absence of TRPC5 antibodies indicated the presence of a current with a reversal potential close to -15 mV. Application of the non-selective TRPC channel blocker, flufenamic acid, had a similar effect, which could be occluded in cells pre-loaded with TRPC5 antibodies. Finally, using the same TRPC5 antibodies we found that most hcrt/orx cells show immunostaining for the TRPC5 subunit. These results suggest that hcrt/orx neurons are endowed with a constitutively active non-selective cation current which depends on TRPC channels containing the TRPC5 subunit and which is responsible for the depolarized and active state of these cells.